Glory and honor to the Armies of the United States of America, liberators of Belgium 1944-1945 - de Baene, Antoine (Bruxelles : J. Rozez, 1948)
Bibliotheek Camille Huysmans
Dedicator: de Baene, Antoine, dedicatee: Huysmans, Camille
Genummerd ex. 35 van 100
Engels
Monografie
Keywords: Wereldoorlog 2; Verenigde Staten; België